Combinatorial effect of Bacillus thuringiensis kurstaki and Photorhabdus luminescens against Spodoptera littoralis (Lepidoptera: Noctuidae). (30th July 2013) - Benfarhat‐Touzri, Dalel; Amira, Amal Ben; khedher, Saoussen Ben; Givaudan, Alain; Jaoua, Samir; Tounsi, Slim
<x xml:space="preserve">Abstract</x> Spodoptera littoralis, one of the major pests of many important crop plants, is more susceptible to Bacillus thuringiensis aizawai delta‐endotoxins than to those of Bacillus thuringiensis kurstaki. Within the framework of the development of efficient bioinsecticides and the prevention against insect resistance, we tested the effect of mixing B. thuringiensis kurstaki delta‐endotoxins and Photorhabdus luminescens cells on S. littoralis growth. The obtained results showed that the growth inhibition of this insect was more effective when B. thuringiensis kurstaki spore‐crystal mixture and Photorhabdus luminescens cells were used in combination. Furthermore, this synergism is mainly due to the presence of Cry1Ac, which is one of the three delta‐endotoxins that form the crystal of B. thuringiensis kurstaki strain BNS3 in addition to Cry1Aa and Cry2Aa. This work shows a possibility to use B. thuringiensis as a delivery means for Photorhabdus bacteria in order to infect the insect hemocoel and to reduce the risk of developing resistance in the target organism.